A influência da presença de nectários extraflorais na estrutura da comunidade de formigas arbóreas do cerrado - Camarota, Flávio de Carvalho (2012)
The extrafloral nectaries (EFN´s) are very important in ant plant interactions, being present in a big number of plant families, mainly in the tropics. However, little is known about the influence of this resource in the structure of the ant community that uses it, except for a few studies in wet tropical forests. The goal of this work was to test and evaluate the importance of nectar resources in the structure of the ant community in a unique and still understudied biome, the Brazilian cerrado, a neotropical savanna. For that, I made a natural experiment and an experimental manipulation in the field, in a reserve located near Uberlândia, Southeastern Brazil. The natural experiment aimed to evaluate the differences in the ant community and the influence of the seasonality of this resource in tree species with and without EFN´s in two periods of the year, one when the EFN´s were mostly inactive (between June and July of 2010) and one in the peak of extrafloral nectar production (between October and November of the same year). For that, I sampled six common species of trees in the cerrado, Caryocar brasiliense, Qualea grandiflora and Stryphnodendron polyphyllum, that have EFN´s and Sclerolobium aureum, Machaerium opacum e Kielmeyeria coriacea, that doesn´t have it. In total, ninety two trees were sampled, ranging from 12 to 18 individuals of each tree species. The sampling was done with the use of pitfall traps, left for 48 hours on the plants. I didn´t find neither any significant differences in ant species richness for plants with or without EFN´s nor any effect for different times of the year. However, at the individual level (plant by plant) there was a bigger species turnover between sampling times in plants with EFN´s than in those without it, the same not been observed when population level was considered. I did an experimental manipulation with the addition of artificial nectaries in two plant species, one that naturally have EFN´s (C. brasiliense) and one that naturally doesn´t have it (S. aureum). I measured the rates of occupation of artificial wood nests (20 nests per tree). The artificial nectaries were made of 2 ml eppendorfs, which were filled weekly with a solution of water, sugar and amino acids, resembling the natural extrafloral nectar constitution. I placed 40 eppendorfs in 20 trees of each plant species, being 10 treatments and 10 controls. The occupation rate was significantly bigger in plant with artificial nectar addition in S. aureum, the same not happening for C. brasiliense. This study shows the need of more studies focusing the importance of EFN´s at the ant community level, in search of direct and indirect factors that influence this importance, like the seasonality of this resource.